Adipose-derived stem cells alleviate liver apoptosis induced by ischemia-reperfusion and laparoscopic hepatectomy in swine. Issue 1 (December 2018) - Ge, Yansong; Zhang, Qianzhen; Li, Hui; Bai, Ge; Jiao, Zhihui; Wang, Hongbin
Abstract Hepatic ischemia-reperfusion (I/R) injury is inevitable during hepatectomy and may cause both postoperative morbidity and mortality. Regenerative medicine suggested adipose-derived stem cells (ADSCs) as an attractive tool for the treatment of liver diseases. In this study, we investigated the effect of ADSCs in an I/R model combined with laparoscopic hepatectomy in swine. Eighteen Bama miniature pigs were randomly divided into Sham, IRI, and ADSCs groups. ADSCs (1 × 106 /kg) were injected through liver parenchyma immediately after hemihepatectomy. The apoptosis-related role of ADSCs was studied. The results showed that ADSCs transplantation reduced both pathological and ultrastructural changes and decreased the number of apoptotic-positive cells. In the ADSCs group, Fas, Fas ligand (FasL) protein, and mRNA were downregulated and the enzyme activities of Caspase3, Caspase8, and Caspase9 were significantly decreased. In addition, ADSC therapy significantly increased the ratio of Bcl-2/Bax protein and mRNA compared to the IRI group. In conclusion, ADSCs attenuated both I/R and hepatectomy-induced liver apoptosis in a porcine model, and offers a potential therapeutic option for hepatic I/R and hepatectomy.